Robustness of VSL Values from Contingent Valuation Surveys - Anna Alberini (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper examines factors that may influence the estimates of the Value of a Statistical Life obtained from contingent valuation surveys that elicit the willingness to pay (WTP) for mortality risk reductions. We examine the importance of distributional assumptions, the choice of the welfare statistics of interest, the procedure for computing them, outliers, undesirable response effects, and internal validity of the WTP responses. We illustrate the importance of these factors using dichotomous-choice and open-ended WTP data from four recent contingent valuation surveys.
Keywords: H41; H51; I18; I31; J17; 330; Contingent valuation; VSL; WTP; Risk reductions; Robustness; Outliers; Endogeneity; Menschen; Bewertung; Zahlungsbereitschaftsanalyse; Sterblichkeit; Risiko; Schätzung; Schweden; Wert des Menschenlebens